2008
DOI: 10.2527/jas.2008-0885
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of rumen ecology by dietary lemongrass (Cymbopogon citratus Stapf.) powder supplementation1

Abstract: This experiment was conducted to investigate the effect of lemongrass [Cymbopogon citratus (DC.) Stapf.] powder (LGP) on rumen ecology, rumen microorganisms, and digestibility of nutrients. Four ruminally fistulated crossbred (Brahman native) beef cattle were randomly assigned according to a 4 x 4 Latin square design. The dietary treatments were LGP supplementation at 0, 100, 200, and 300 g/d with urea-treated rice straw (5%) fed to allow ad libitum intake. Digestibilities of DM, ether extract, and NDF were si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
52
3
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 27 publications
18
52
3
3
Order By: Relevance
“…The VFA concentrations or molar proportions of VFA were not affected by the treatments (P > 0.05). Total VFA concentrations in all treatments ranged from 121.2 to 128.4 mM and were similar to those reported by Wanapat et al (2008Wanapat et al ( , 2009a.…”
Section: Characteristics Of Ruminal Fermentation and Blood Metabolitessupporting
confidence: 71%
“…The VFA concentrations or molar proportions of VFA were not affected by the treatments (P > 0.05). Total VFA concentrations in all treatments ranged from 121.2 to 128.4 mM and were similar to those reported by Wanapat et al (2008Wanapat et al ( , 2009a.…”
Section: Characteristics Of Ruminal Fermentation and Blood Metabolitessupporting
confidence: 71%
“…In an in vivo study in swamp buffalo, garlic powder reduced rumen protozoal population by 44.1% as compared to control group. In our study with native beef cattle, lemongrass powder supplementation reduced protozoal population by 23.8% (Wanapat et al 2008a). Recently, Machmüller et al (2003) suggested that supplementation of coconut oil tended to reduce the population of bacteria and ciliate protozoa in sheep rumen.…”
Section: Rumen Microorganisms Populationmentioning
confidence: 73%
“…In addition, higher ruminal pH and ammonia-nitrogen concentration have been found as compared to those in cattle indicating higher rumen N-recycling (Wanapat et al, 2003). Manipulation of diets will enhance rumen fermentation and subsequent uses by the ruminants (Thu and Preston, 1999;Wanapat, 2000Wanapat, , 2001Wanapat and Rowlinson, 2007;Wanapat et al, 2008). Buffalo meat consisted of crimson, bigger muscle fiber thickness and with white fat while cattle meat has vermilion, powdery and yellow fat (Valin et al, 1984).…”
Section: Introductionmentioning
confidence: 94%